Predicting Required COVID-19 Vaccine Coverage and its Impact in Sierra Leone Using Mathematical Models - Kamara, Joseph AL; Kamara, Abdul A; Samura, Sallieu K (Archives of Clinical and Biomedical Research, 2022)
In this article, we predict the required vaccine coverage for the COVID-19 outbreak in Sierra Leone. We also, investigate the impact of facemask and vaccine coverage on the spread of the COVID-19 virus using modified Symptomatic-Asymptomatic Infection Transmissions Susceptible-Latent-Infectious-Asymptomatic-Recovered (SLIAR) model. We derived an explicit formula for the basic reproduction number and used it to understand the dynamics of the disease when it is greater than unity. We also used the Maximum Likelihood modelling technique to estimate the basic reproduction number using incidence data. Numerically, we show that 58 per cent of the Sierra Leone national population required vaccination for the COVID-19 virus. Also, the SLIAR with vaccine model results reveals that the impact of using facemask is very challenging to understand and the vaccine coverage decrease the infected transmission rate but cannot completely stop the infection.